log(x-9)+log(x+9)=2

Simple and best practice solution for log(x-9)+log(x+9)=2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for log(x-9)+log(x+9)=2 equation:


Simplifying
log(x + -9) + log(x + 9) = 2

Reorder the terms:
glo(-9 + x) + log(x + 9) = 2
(-9 * glo + x * glo) + log(x + 9) = 2
(-9glo + glox) + log(x + 9) = 2

Reorder the terms:
-9glo + glox + glo(9 + x) = 2
-9glo + glox + (9 * glo + x * glo) = 2
-9glo + glox + (9glo + glox) = 2

Reorder the terms:
-9glo + 9glo + glox + glox = 2

Combine like terms: -9glo + 9glo = 0
0 + glox + glox = 2
glox + glox = 2

Combine like terms: glox + glox = 2glox
2glox = 2

Solving
2glox = 2

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Divide each side by '2lox'.
g = l-1o-1x-1

Simplifying
g = l-1o-1x-1

See similar equations:

| (7b-1)-2(3b+4)=-6 | | 7x+3=7+3 | | -9(3b+1)+(28b-3)=0 | | 2x^2+x=100 | | 2x^2+x-100=0 | | 12v^2+12v-6=0 | | F(x)=-3x+11 | | 2x^2+12x-210=0 | | 13x+16-x=4 | | 9(x+2)=23 | | I=PRTfort | | 1801=16t^2 | | 3x^2+x-324=0 | | 3x+25=45 | | U=4(3n+35)+9(n+1) | | 45-2= | | 3x-83=0 | | x(x+1)=2409 | | 2(4g+39)-8g-78=0 | | 4a+6a+8+5= | | 3m+7m= | | 0.5x-0.2(40+x)=0.4(40) | | 1968=16t^2 | | 20=-2(m+3)+3 | | y=0.5x^2-3x | | 0.6x+14.3=x-8.62 | | 3(2x-2.2)=8x-6.6 | | -0.5x+2.35=-0.1x+9.95 | | -0.5x+2.35=-0.1+9.95 | | 4-6y=21y-13 | | 4.9+0.9x=0.4 | | 7x-10=8x-6 |

Equations solver categories